Dependence of dielectric barrier discharge jet length on gas flow rate and applied voltage - Lau, Y.T.; Jayapalan, K.K.; Pam, M.E.; Chin, Oi Hoong; Wong, Chiow San (Akademi Sains Malaysia & Confederation of Scientific & Technological Association in Malaysia (COSTAM), 2014)
The effect of gas flow rate of helium and argon on the length of dielectric barrier discharge (DBD) jet generated under atmospheric pressure using an AC source is investigated. It is found that as the flow rate increases, the jet length increases up to a maximum length. Upon further increase in flow rate, it will cause the jet length to decrease. Visual inspection shows the jet to be of laminar flow when its length was increasing, and gets turbulent when the jet length decreases with increased flow rate. There is an obvious increment in jet length of argon DBD system when the applied voltage is increased from 8.8 kV to 11.0 kV, but not in helium. Spectral analysis reveals the DBD jet to comprise of emission lines of its constituent flow gas. In addition to that, emission lines of component gases (N2 and O) in ambient air and water vapour were also present. Upstream jet was obtained only in helium DBD jet at low flow rate but high applied voltage.